Metal powder for magnetic force combined 3D printing and preparation method thereof
By adjusting the element ratio and processing technology of austenitic steel powder, low-cost and efficient magnetic regulation in 3D printing is achieved, and pore defects and environmental pollution problems in adhesive spraying technology are solved, satisfying the magnetic combination 3D printing technical requirements.
Patent Information
- Application Number
- CN202411306412.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-19
AI Technical Summary
The existing adhesive jet 3D printing technology is prone to pore defects, environmental pollution and cleaning in casting, and it is difficult to achieve simple and efficient magnetic regulation of 3D printing.
Using an austenitic steel metal powder, the content ratio of elements such as Cr, Ni, Mn is adjusted, so that the martensite start transition temperature is lower than the 3D printing powder laying temperature, and the maximum temperature of strain-induced martensite transformation is higher than that of The powder laying temperature and layering error energy are greater than or equal to 18mJ/m2. The mechanical driving force and temperature driving force are used to achieve magnetic transformation of the material during 3D printing, and magnetic regulation is achieved through casting/shooting peening and heat treatment.
It realizes efficient magnetic regulation without a large amount of adhesive in 3D printing, reduces costs, simplifies the process, improves the stability of the material and the magnetic transformation speed, and meets the requirements of magnetic combined with 3D printing technology.
Smart Images

Figure CN119187542A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of 3D printing, and in particular to a metal powder for magnetically combined 3D printing and a preparation method thereof. Background Art
[0002] Additive manufacturing technology is one of the current advanced manufacturing technologies. The main types include fused deposition modeling, laser additive manufacturing, electron beam melting modeling, binder jetting, etc. Among them, binder jetting has been widely used in moldless molding in casting production. However, the cost of using binders is high, and it is easy to produce porosity defects in castings, which will cause environmental pollution and difficult to clean. The new magnetic force combined with 3D printing technology combines the model into a whole through the magnetic force under the magnetic field to replace or reduce the use of binders, which can solve the above-mentioned problems. The key to the realization of the new magnetic force combined with 3D printing technology is the need for a powder material that can be regulated by a magnetic optional area.
[0003] At present, the magnetic transformation methods that are studied more are mainly chemical doping, crystal transformation, high-temperature oxidation, etc., but these methods have many difficulties in applying magnetic force combined with 3D printing technology. It is still necessary to develop a powder material that can achieve simple and efficient magnetic control in 3D printing. Metastable austenitic steel will show different magnetic properties according to different organizational structures. The martensite phase of the body-centered cubic structure (BCC) is ferromagnetic, while the austenite phase of the face-centered cubic structure (FCC) is paramagnetic. Under a certain driving force, the austenite phase in metastable austenitic steel can rapidly undergo martensite phase transformation, which can be developed into a way to efficiently achieve material magnetic control. However, since the research is mainly focused on avoiding phase transformation in austenitic steel to improve stability or making partial phase transformation to improve the mechanical properties of the material, the magnetic transformation characteristics caused by phase transformation have not yet been fully utilized.
[0004] Therefore, by adjusting the content ratio of elements such as Cr, Ni, and Mn in austenitic steel, a metastable austenitic steel powder was studied, designed, and prepared. Under a smaller driving force, more martensite phase transformation amounts can be achieved to produce magnetism, and after heat treatment, it can return to the austenite phase to achieve demagnetization, giving full play to the magnetic change characteristics caused by the phase transformation of austenitic steel, so that it can be applied to magnetic combined with 3D printing technology, which has important application value. Summary of the invention
[0005] In view of the problems that the existing jet binder 3D printing technology causes pore defects, environmental pollution, and high cleaning difficulty when used for casting, the present invention provides a metal powder for magnetically combined 3D printing. The magnetic selectable area of the metal powder material is regulated, and the model is combined into a whole through the magnetic force under the magnetic field to replace or reduce the use of binders. At the same time, the present invention also provides a method for preparing metal powder for magnetically combined 3D printing.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0007] On the one hand, the present invention provides a metal powder for magnetic combined 3D printing, wherein the metal powder is an austenitic steel metal powder, which is basically non-magnetic in the initial state, can generate magnetism after being subjected to force, and can return to being basically non-magnetic after heat treatment.
[0008] Furthermore, the martensitic transformation temperature of the austenitic steel metal powder is lower than the 3D printing powder spreading temperature, the maximum temperature of the strain-induced martensitic transformation is higher than the 3D printing powder spreading temperature, and the stacking fault energy is greater than or equal to 18 mJ / m 2 , the nickel equivalent and chromium equivalent are in the austenite phase region on the Schaeffler organization diagram.
[0009] In another aspect, the present invention provides a method for preparing metal powder for magnetically coupled 3D printing, comprising the following steps:
[0010] S1. Design the composition of metal materials so that their martensitic transformation temperature is lower than the 3D printing powder laying temperature, their strain-induced martensitic transformation maximum temperature is higher than the 3D printing powder laying temperature, and their stacking fault energy is greater than or equal to 18mJ / m 2 , the nickel equivalent and the chromium equivalent are in the austenite phase region on the Schaeffler organization diagram;
[0011] S2. Melting: melting metal materials according to the designed composition;
[0012] S3, powder processing, converting the smelted metal into metal powder;
[0013] S4, subjecting the metal powder to a solution treatment and a water quenching treatment to obtain a substantially non-magnetic metal powder;
[0014] S5. Make the basically non-magnetic metal powder generate magnetism after being subjected to force.
[0015] Further, the step S1 of designing the metal material composition comprises the following steps:
[0016] S11. Component range of preliminary design materials;
[0017] S12, calculating the martensitic transformation temperature of the material, and selecting a composition range whose martensitic transformation temperature is lower than the 3D printing powder laying temperature;
[0018] S13, within the composition range selected in step S12, calculating the maximum temperature of the strain-induced martensitic transformation of the material, and selecting a composition range in which the maximum temperature of the strain-induced martensitic transformation is higher than the 3D printing powder laying temperature;
[0019] S14: Calculate the stacking fault energy of the material within the range of components selected in step S13, and select a stacking fault energy greater than or equal to 18 mJ / m 2 The range of ingredients;
[0020] S15, within the component range selected in step S14, calculating the nickel equivalent and the chromium equivalent of the material, and selecting a component range in which the nickel equivalent and the chromium equivalent are in the austenite phase region on the Schaeffler organization diagram;
[0021] S16. Calculate the chromium-nickel ratio of the material within the range of components screened in step S15, sort the components screened in step S15 according to the chromium-nickel ratio, and select the components with the highest chromium-nickel ratio.
[0022] Further, the maximum temperature of the strain-induced martensitic transformation of the material in step S1 is denoted by M d30 Representative, M. d30 That is, the temperature at which austenite transforms to 50% martensite when the true strain is 30%; the stacking fault energy of the material in step S1 is represent, is the stacking fault energy at room temperature 300K.
[0023] Further, the martensitic transformation start temperature of the material is calculated as follows:
[0024] M s =1350-1655(w C +w N )-33w Mn -28w Si -42w Cr -61w Ni
[0025] The maximum temperature of the strain-induced martensitic transformation of the material is calculated as follows:
[0026] M d30 =413-462(w C +w N )-8.1w Mn -9.2w Si -13.7w Cr -9.5w Ni -18.5w Mo
[0027] The stacking fault energy of the material is calculated as follows:
[0028]
[0029] The nickel equivalent of the materials is calculated as follows:
[0030] Ni eq =w Ni+30(w C +w N )+0.5(w Mn +w Cu +w Co )
[0031] The chromium equivalent of the materials is calculated as follows:
[0032] Cr eq =w Cr +1.5w Si +w Mo
[0033] Among them, w C 、w N 、w Mn 、w Si 、w Cr 、w Ni 、w Mo 、w Cu 、w Co Respectively represent the weight percentage of C, N, Mn, Si, Cr, Ni, Mo, Cu, and Co elements in the metal alloy; is the stacking fault energy at room temperature 300K, is the stacking fault energy of pure γ-Fe at room temperature.
[0034] Furthermore, the smelting in step S2 is vacuum induction melting.
[0035] Furthermore, the powder processing in step S3 is performed by inert gas atomization.
[0036] Furthermore, in step S5, the method of causing the substantially non-magnetic metal powder to generate magnetism after being subjected to force is shot blasting / shot peening.
[0037] Furthermore, the spraying speed of the metal powder material during the shot blasting / shot peening process is 10-160 m / s.
[0038] Compared with the prior art, the metal powder for magnetic-coupled 3D printing provided by the present invention has characteristic indicators that can meet the requirements of magnetic-coupled 3D printing technology for powder-laying materials and is easy to achieve industrial preparation; the metal powder preparation method for magnetic-coupled 3D printing provided by the present invention can achieve quantitative and precise design of components, the process has strong operability, and is easy to achieve computer screening. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a flow chart of the new magnetic combined 3D printing production process involved in the present invention.
[0040] Figure 2 It is a flow chart of the method for preparing metal powder for magnetic combined 3D printing provided by the present invention.
[0041] Figure 3 is the M of the material under different compositions of the embodiments provided by the present invention s and M d30 Isotherm diagram.
[0042] Figure 4 1 is a stacking fault energy diagram of materials with different compositions according to an embodiment of the present invention.
[0043] Figure 5 1 is an organizational chart of Schaeffler involved in the embodiment of the present invention.
[0044] Figure 6 This is the austenite phase region range of the material provided by the embodiment of the present invention.
[0045] Figure 7 It is a phase comparison diagram of the material provided by the embodiment of the present invention after stress and heat treatment.
[0046] Figure 8 This is a diagram of the change in magnetic gravity of the material after stress and heat treatment provided by an embodiment of the present invention. DETAILED DESCRIPTION
[0047] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further explained below with reference to specific diagrams.
[0048] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "model", "magnetization" and "non-magnetic" should be understood in a broad sense. For example, non-magnetic also includes low magnetism that is close to non-magnetic in engineering practice. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0049] The new magnetic force combined with 3D printing production process flow chart of the present invention is as follows Figure 1 As shown, after spreading the powder, a selective magnetic transformation is required to make the powder material in the casting area magnetic and the rest non-magnetic, so that a magnetic field can be applied after layer-by-layer printing is completed to obtain a casting model.
[0050] The present invention uses an indirect method to achieve selective magnetic transformation, and the process is divided into two steps: pretreatment before powder spreading, all non-magnetic austenitic steel metal powders are transformed into magnetism by force-induced martensite phase transformation; after the powder spreading is completed, selective laser heating treatment is performed to restore the generated martensite to austenite, and the non-target area is transformed into non-magnetic. The present invention utilizes the martensite transformation in austenitic steel and its reversibility to make the material undergo magnetic transformation between magnetism and non-magnetism, and has the advantages of low cost, simple method, and fast transformation speed.
[0051] As a specific embodiment, the present invention provides a metal powder for magnetic combined 3D printing, wherein the metal powder is an austenitic steel metal powder, which is basically non-magnetic in the initial state, can generate magnetism after being subjected to force, and can return to being basically non-magnetic after being heated.
[0052] The main reason is that in order to transform austenitic steel from non-magnetic to magnetic, the austenite structure needs to be transformed into a martensite structure, and this phase change can rely on mechanical driving force and temperature driving force. If relying on temperature driving force, the typical treatment process is quenching, but the martensite produced in this way will return to austenite when the temperature reaches the 3D printing powder spreading temperature, and the magnetism will disappear. If relying on mechanical driving force to subject the material to force, the typical process is such as blasting / shot peening, and the martensite produced will not return to austenite when the temperature reaches the 3D printing powder spreading temperature, and the magnetism will not disappear. The magnetic martensite produced by the mechanical driving force will disappear during the selective heating treatment, and the magnetic martensite will return to non-magnetic austenite. The present invention cleverly utilizes the difference between mechanical driving force and temperature driving force, and can achieve magnetic martensite before selective heating treatment at the same 3D printing powder spreading temperature, and non-magnetic austenite after selective heating treatment, solving the problem of 3D printing magnetic selection regulation.
[0053] In one embodiment, the martensitic transformation temperature of the austenitic steel metal powder is lower than the 3D printing powder spreading temperature, the maximum temperature of the strain-induced martensitic transformation is higher than the 3D printing powder spreading temperature, and the stacking fault energy is greater than or equal to 18 mJ / m 2 , the nickel equivalent and chromium equivalent are in the austenite phase region on the Schaeffler organization diagram.
[0054] The main reason for adopting the above-mentioned technical means is that the austenitic steel powder must have the following characteristics during use: during pretreatment before powder spreading, the material needs to be transformed from non-magnetic to magnetic, and as much martensitic phase change as possible should be produced under a smaller mechanical driving force, and can be maintained to the 3D printing powder spreading temperature, which requires that the maximum temperature of the strain-induced martensitic transformation of the material is higher than the 3D printing powder spreading temperature; during selective heat treatment of non-target areas, the material that has undergone martensitic transformation must be transformed into non-magnetic, and as much reversed austenite as possible should be obtained, and can be maintained to the 3D printing powder spreading temperature, which requires that the martensitic start transformation temperature of the material is lower than the 3D printing powder spreading temperature.
[0055] In one embodiment, the important parameter definitions related to the martensitic phase transformation and the calculation formulas used are as follows:
[0056] (1) Martensite transformation temperature in austenitic steel (M s )
[0057] Ms The physical meaning of is the difference in free energy between austenite and martensite. The temperature at which the minimum driving force required for phase transformation is reached may reflect the minimum undercooling for martensite transformation. Therefore, when the metastable austenitic steel is cooled to a certain temperature, whether the austenite can be transformed into martensite structure should refer to M s . M s At the same time, it reflects the stability of austenite. s The lower the point, the higher the stability of the austenitic steel.
[0058] Steel M s The temperature is related to many factors such as the degree of alloying, the degree of austenitization after heating and holding, and the grain size, among which the most important influencing factor is its chemical composition. The present invention adopts a quantitative empirical formula established by using a statistical method as one of the guiding bases for alloy design. Specifically, the martensitic transformation temperature of the material is calculated as follows:
[0059] M s =1350-1655(w C +w N )-33w Mn -28w Si -42w Cr -61w Ni
[0060] Among them, w C 、w N 、w Mn 、w Si 、w Cr 、w Ni They represent the weight percentage of C, N, Mn, Si, Cr and Ni elements in the metal alloy respectively.
[0061] (2) The maximum temperature of strain-induced martensitic transformation (M d )
[0062] M d The physical meaning of is the highest temperature at which strain-induced martensitic transformation occurs, that is, when the temperature is higher than M d Temperature, although plastic deformation occurs, no martensitic transformation occurs. d It can also be used to determine the stability of austenite, the thermodynamic conditions for martensite transformation at a certain temperature, and the final transformation amount of martensite.
[0063] Due to M d It is difficult to measure experimentally, M d30 Temperature point can replace M d , that is, the temperature at which austenite transforms to 50% martensite when the true strain is 30%. d30 The higher the value of M, the lower the stability of the metastable austenitic steel.s Whether deformation will induce martensitic transformation within a certain temperature range above the point needs to refer to the M of austenitic steel. d30 In order to ensure that the metastable austenitic steel undergoes martensitic transformation through mechanical impact treatment at the powder spreading temperature, M d30 It should be higher than the powder spreading temperature; in order to make the metastable austenitic steel produce more martensite under a smaller mechanical driving force, the stability of austenite should be lower, M d30 The higher the better within the appropriate range. The present invention selects an empirical formula to calculate M d30 , the maximum temperature of strain-induced martensitic transformation of the specific material is calculated as follows:
[0064] M d30 =413-462(w C +w N )-8.1w Mn -9.2w Si -13.7w Cr -9.5w Ni -18.5w Mo
[0065] Among them, w C 、w N 、w Mn 、w Si 、w Cr 、w Ni 、w Mo They represent the weight percentage of C, N, Mn, Si, Cr, Ni and Mo elements in the metal alloy respectively.
[0066] (3) Stacking fault energy (γ sf )
[0067] γ sf It is an important intrinsic parameter that affects the phase transformation, deformation and performance of austenite. It refers to the energy difference between atoms in the stacking fault and normal stacking. It is calculated by measuring the stacking fault width and using the formula derived from the dislocation theory. It reflects the strain energy caused by the stacking fault and the Suzuki effect caused by the segregation of alloy elements.
[0068] γ sf Affects the transformation sequence of strain-induced martensitic transformation: when the γ sf Less than 18mJ / m 2 When the γ phase is indirectly converted to α', the path is γ→ε→α', which is not conducive to improving magnetic properties. sf Greater than or equal to 18mJ / m 2 When the γ phase is directly transformed into α', the path is γ→austenite twin→α', which is beneficial to improving magnetic properties.
[0069] The present invention selects the following empirical formula to calculate the γsf , the stacking fault energy of the specific material is calculated as follows:
[0070]
[0071] in, is the stacking fault energy at room temperature 300K, is the stacking fault energy of pure γ-Fe at room temperature, which is about 0.036~0.042mJ / m 2 , calculate the middle value of 0.039mJ / m 2 The applicable alloy composition range of this formula is: Mn≤40%, Cr≤25%, Ni≤23%, Mo≤2%, Si≤4%, C+N≤0.45%, and the total amount of alloy elements ≤45%. sf Should be ≥18mJ / m 2 , tends to directly produce α' martensite.
[0072] (4) Nickel equivalent (Ni eq ) and chromium equivalent (Cr eq )
[0073] Chromium-nickel equivalent phase balance is the basic theoretical basis for steel alloying. The composition equivalent method measures the contribution of alloying elements to the structural stability of austenitic steel using Cr equivalent and Ni equivalent. The contribution of a certain alloying element to the stability of the matrix can be calculated by multiplying its mass percentage by the equivalent coefficient. Combined with the Schaeffler organization chart, the structural stability of austenitic steel can be judged and the organization can be predicted. In the Schaeffler organization chart, only when the Cr and Ni equivalents of the designed alloying elements fall in the austenite phase region can a single austenite structure be obtained after alloying.
[0074] The target steel composition needs to maintain a stable austenite structure at the powder spreading temperature, so Ni is required on the Schaeffler organization diagram. eq and Cr eq Falling within the austenite phase region; the stability of austenitic steel is lower, and the nickel equivalent should be as low as possible within an appropriate range.
[0075] The present invention determines the stability of austenitic steel based on the empirical calculation formula of the minimum equivalent of nickel in austenitic steel:
[0076] Ni eqmin =(w Cr +1.5w Mo -20) 2 / 12-w Mn / 2-35w C +15
[0077] Δγ represents the stability of austenite, Δγ=Ni%-Ni eqminIf Δγ≥0, it is stable; if Δγ<0, it is intermediate stable.
[0078] The composition design needs to predict the organization based on the Schaeffler organization diagram to ensure that the steady-state organization of the steel is single-phase austenite. The nickel equivalent of the material is calculated as follows:
[0079] Ni eq =w Ni +30(w C +w N )+0.5(w Mn +w Cu +w Co )
[0080] The chromium equivalent of the materials is calculated as follows:
[0081] Cr eq =w Cr +1.5w Si +w Mo
[0082] Among them, w C 、w N 、w Mn 、w Si 、w Cr 、w Ni 、w Mo 、w Cu 、w Co They represent the weight percentage of C, N, Mn, Si, Cr, Ni, Mo, Cu and Co elements in the metal alloy respectively.
[0083] (5) Chromium-nickel ratio (Cr / Ni)
[0084] Metastable austenitic steel produces a large amount of martensite after deformation. When annealed at an appropriate temperature, martensite reverses to austenite, but the chromium-nickel ratio in the composition will affect the transformation mechanism. When the chromium-nickel ratio is high, the reverse transformation of martensite to austenite occurs in a diffusion manner, and when the chromium-nickel ratio is low, the reverse transformation occurs in a non-diffusion shear manner. Shear reverse transformation has a lower transformation temperature and a faster transformation speed than diffusion transformation. Under the premise of ensuring that the composition meets the above conditions, the reverse transformation of martensite should be carried out quickly. Therefore, when designing, priority should be given to those with a high nickel-chromium ratio to achieve a phase transformation mechanism dominated by shear reverse phase transformation.
[0085] As another specific embodiment, please refer to Figure 2 As shown, the present invention provides a method for preparing metal powder for magnetically combined 3D printing, comprising the following steps:
[0086] S1. Design the metal material composition. The 3D printing powder spreading temperature of this embodiment is 30°C, so that its martensite start transformation temperature is lower than the 3D printing powder spreading temperature, and its maximum temperature of strain-induced martensite transformation is higher than the 3D printing powder spreading temperature, so that its stacking fault energy is greater than or equal to 18mJ / m 2 , the nickel equivalent and the chromium equivalent are in the austenite phase region on the Schaeffler organization diagram;
[0087] S2. Melting: melting metal materials according to the designed composition;
[0088] S3, powder processing, converting the smelted metal into metal powder;
[0089] S4, subjecting the metal powder to a solution treatment and a water quenching treatment to obtain a substantially non-magnetic metal powder;
[0090] S5. Make the basically non-magnetic metal powder generate magnetism after being subjected to force.
[0091] In one embodiment, the step S1 of designing the metal material composition comprises the following steps:
[0092] S11. Preliminary design of material composition range; in this embodiment, the preliminary design of material composition range is Cr: 16-19wt%, Ni: 6-10wt%, Mn: 1-2wt%, Mo: 0.375wt%, Si: 0.5wt%, C: 0.075wt%, S: 0.15wt%, P: 0.0225wt%.
[0093] S12. Calculate the martensitic transformation start temperature of the material, and select a composition range whose martensitic transformation start temperature is lower than the 3D printing powder laying temperature.
[0094] S13, within the composition range selected in step S12, calculating the maximum temperature of the strain-induced martensitic transformation of the material, and selecting a composition range in which the maximum temperature of the strain-induced martensitic transformation is higher than the 3D printing powder laying temperature;
[0095] Figure 3 is the M of the material under different compositions in this embodiment s and M d30 Isotherm plot, Figure 3 Each solid line on the graph represents a different M s The isotherms and the corresponding content ranges of the three alloy elements Cr, Ni and Mn. As the Mn content increases, s The isotherm keeps moving to the left, which means that M s The upper limit target range (≤-30℃) is continuously expanding the range of Cr and Ni content available for screening. s The impact is greater. Figure 3Each dotted line on the graph represents a different M d30 The isotherms and the corresponding content ranges of the three alloy elements Cr, Ni and Mn. As the Mn content increases, d30 The isotherm keeps moving to the left, which means that M d30 The lower limit target range (≥45℃) for screening Cr and Ni content ranges is shrinking. Under the same Mn content, Cr content has a significant impact on Mn content. d30 The impact is greater. Figure 3 The material composition of the intersection can satisfy M s <-30℃ and M d30 ≥45℃ condition. d30 Dot and M s The point basically increases or decreases simultaneously with the change of composition. d30 Dot or M s The higher the point, the more unstable the austenite steel under this composition is. Therefore, within the range that meets the conditions, M d30 Dot and M s The higher the point, the better.
[0096] S14: Calculate the stacking fault energy of the material within the range of components selected in step S13, and select a stacking fault energy greater than or equal to 18 mJ / m 2 The range of ingredients;
[0097] Figure 4 The stacking fault energy diagram of the material under different compositions provided in the embodiment of the present invention is shown in Figure 1. The material needs to directly form α' martensite under the driving force and minimize the formation of the intermediate phase. Therefore, the target composition should be selected in the region with higher stacking fault energy (≥18mJ / m 2 ) and the higher the better. Calculate the γ of all components within the range sf All greater than 18mJ / m 2 , under the same Cr and Ni contents, with the increase of Mn content, the γ sf When the Mn content is 1.0wt%, the intersection area is the largest and the γ sf is the largest, so the Mn content is selected as 1.0wt%.
[0098] S15, within the component range selected in step S14, calculating the nickel equivalent and the chromium equivalent of the material, and selecting a component range in which the nickel equivalent and the chromium equivalent are in the austenite phase region on the Schaeffler organization diagram;
[0099] Figure 5 is the Schaeffler organization diagram involved in the embodiment of the present invention, and the Cr of the material is calculated according to the formula eq and Ni eq . Calculation range selection Figure 4The Mn content is 1.0wt% and satisfies M s <-30℃ and M d30 ≥45℃ intersection rectangular area. This intersection rectangular area corresponds to Figure 5 The red dashed rectangular area in the Schaeffler organizational chart.
[0100] S16. Within the range of components screened in step S15, calculate the chromium-nickel ratio of the material and select components with a higher chromium-nickel ratio.
[0101] Figure 6 This is the austenite phase region range of the material provided in the embodiment of the present invention. It is necessary to select the composition range of the austenite region to ensure that the material maintains a single austenite structure at room temperature.
[0102] In order to realize the phase transition mechanism dominated by shear reverse phase transition in the subsequent reverse transformation process, the Cr / Ni with higher Cr / Ni ratio should be given priority under the premise of meeting other conditions, that is, Figure 6 Target component area.
[0103] Calculated according to the formula Figure 6 Ni in the target composition area eqmin and Δγ, all Δγ are less than 0, indicating that the stability of all austenitic steels within the selected composition range tends to be metastable.
[0104] In summary, the final designed material composition ranges are: Cr: 16.1-16.5wt%, Ni: 8.7-9.1wt%, Mn: 1.0wt%, Mo: 0.375wt%, Si: 0.5wt%, C: 0.075wt%, S: 0.15wt%, P: 0.0225wt%. , M s 、M d30 , γ sf 、Ni eq Cr eq They are -39.13℃, 48.75℃, and 51.61mJ / m 2 , 11.15%, 17.93%, which meets claim 2.
[0105] In one embodiment, the maximum temperature of the strain-induced martensitic transformation of the material in step S1 is denoted by M. d30 Representative, M. d30 That is, the temperature at which austenite transforms to 50% martensite when the true strain is 30%; the stacking fault energy of the material in step S1 is represent, is the stacking fault energy at room temperature 300K.
[0106] In one embodiment, the smelting in step S2 is vacuum induction melting, which can reduce the oxidation of alloy elements and ensure the accuracy of chemical composition.
[0107] In one embodiment, the powder processing in step S3 is inert gas atomization, thereby reducing surface oxidation of the powder material, increasing the fluidity of the powder material, and making the preparation process mature and reliable.
[0108] In one embodiment, the method of making the substantially non-magnetic metal powder generate magnetism after being subjected to stress in step S5 is shot blasting / shot peening. Shot peening is a surface strengthening process widely used in existing factories, that is, a cold processing process that uses pellets to bombard the surface of the workpiece and implant residual stress to improve the fatigue strength of the workpiece. It is widely used to improve the mechanical strength, wear resistance, fatigue resistance and corrosion resistance of parts, and is particularly suitable for the stress processing of powder granular materials. Therefore, the specific process of making the non-magnetic granular material in the initial state generate magnetism after being subjected to stress deformation by shot peening is well known to those skilled in the art and will not be described here.
[0109] In one embodiment, the spraying speed of the metal powder material for shot blasting / peening is 10-160 m / s, and the numerical range is to adapt to the composition change of the metastable austenitic steel powder material.
[0110] In order to better understand the technical solution provided by the present invention, it will be further described below with reference to specific examples.
[0111] One aspect of the present invention provides a 0.75Cr16.3Ni8.9 steel powder for magnetic combined 3D printing technology. The components used in the material include, by mass percentage: Ni: 8.9wt%, Cr: 16.3wt%, Mn: 1.0wt%, Mo: 0.375wt%, Si: 0.5wt%, C: 0.075wt%, S: 0.15wt%, P: 0.0225wt%, other unspecified elements, each ≤0.02wt%, total ≤0.10wt%, and the rest is Fe.
[0112] In the above technical solution, the 0.75Cr16.3Ni8.9 powder is spherical, with a sphericity greater than 95%, a hollow ball rate not exceeding 3%, an oxygen content of the powder below 0.05%, a particle size distribution of 0.5 to 1 mm, and a bulk density of 4.10 to 4.25 g / cm 3 , fluidity is 26.2~27.4s / 50g;
[0113] Preferably, in the above technical solution, the 0.75Cr16.3Ni8.9 steel powder consists of an austenite phase.
[0114] Another aspect of the present invention provides a method for preparing the above-mentioned 0.75Cr16.3Ni8.9 metastable austenitic steel powder, which is first prepared into a steel ingot by vacuum induction melting, and then prepared by vacuum induction melting inert gas atomization method (VIGA), characterized in that the preparation method comprises the following steps:
[0115] Step 1, smelting and preparation, mixing the raw materials according to the above ratio and then smelting and casting by vacuum induction melting to initially produce as-cast 0.75Cr16.3Ni8.9 austenitic steel;
[0116] Step 2: homogenization treatment, subjecting the as-cast steel ingot with the riser cut off and the surface oxide layer removed to homogenization treatment to eliminate possible component segregation in the steel ingot;
[0117] Step 3, powder processing, placing the 0.75Cr16.3Ni8.9 austenitic steel rod into a vacuum induction inert gas atomization powder making device, preparing the pre-0.75Cr16.3Ni8.9 powder by gas atomization, then sieving the pre-0.75Cr16.3Ni8.9 powder to remove large particles, and then drying in a vacuum drying oven to obtain spherical 0.75Cr16.3Ni8.9 powder;
[0118] Step 4: Solution treatment: solution treatment is performed in an atmosphere heating furnace, followed by water quenching.
[0119] Furthermore, in step 1, the temperature of the molten steel is raised to 1650-1685°C.
[0120] Furthermore, in step 1, the smelting device is a medium frequency vacuum induction furnace.
[0121] Furthermore, in the step 1, the process of crushing and mixing components is also included before smelting; and smelting includes pretreatment, roughing and refining processes performed in sequence.
[0122] Furthermore, in step 2, the homogenization treatment temperature is 400° C. and the time is 4 hours.
[0123] Furthermore, in step 3, the oxygen content is controlled within 600 ppm during the entire process.
[0124] Furthermore, in step 3, the drying temperature set in the vacuum drying oven is 100° C. and the drying time is more than 2 hours.
[0125] Furthermore, in step 3, the obtained 0.75Cr16.3Ni8.9 powder has a particle size of 50-150 μm and a sphericity of more than 95%.
[0126] Furthermore, the step 3 includes a final smelting temperature of 1620-1635° C., a vacuum degree of less than 10 Pa, and an atomization pressure of 9.0-12.5 MPa.
[0127] Furthermore, in step 3, the powder processing and preparation method also includes mechanical ball milling, CNC machining, etc.
[0128] Furthermore, in step 4, the solution treatment is carried out under a protective atmosphere, the heat treatment temperature is 1050° C., and the time is 30 min;
[0129] Furthermore, the experiment in step 4 needs to be carried out under vacuum conditions, and the protective atmosphere includes at least one of argon, helium, and nitrogen atmospheres.
[0130] Figure 7 This is a measured phase comparison diagram of the material provided in the embodiment of the present invention after stress and heat treatment. It can be seen that martensite is produced in the material after stress, and the martensite returns to austenite after heat treatment.
[0131] Figure 8 This is a measured magnetic-gravity change diagram of the material provided in the embodiment of the present invention after stress and heat treatment. It can be seen that the material is basically non-magnetic in the initial state, magnetism is generated after stress treatment, and it returns to basically non-magnetic after heat treatment.
[0132] Compared with the prior art, the present invention has the following significant advantages:
[0133] 1. The characteristic indexes of the metal powder prepared by the present invention can meet the requirements of magnetic force combined with 3D printing technology for powder spreading materials, and it is easy to realize industrial preparation. The preparation technology has application prospects for industrial preparation.
[0134] 2. The metal powder prepared by the present invention, due to the design of the components and the adjustment of the proportion, plays a role in regulating the stability of austenite and improving the trend of martensite phase transformation, so that the powder sample has the advantage of adjustable magnetic properties, and efficiently realizes the requirement of magnetic transformation of the powder material in the magnetic combined 3D printing technology.
[0135] 3. The metal powder preparation method provided by the present invention can realize the quantitative and precise design of the components, the process is highly operable, and it is easy to realize computer screening.
[0136] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A metal powder for magnetically coupled 3D printing, characterized in that: The metal powder is an austenitic steel metal powder, which is basically non-magnetic in the initial state, can generate magnetism after being subjected to force, and can return to being basically non-magnetic after being heated.
2. The metal powder for magnetically coupled 3D printing according to claim 1, characterized in that: The martensite transformation start temperature of the austenitic steel metal powder is lower than the 3D printing powder spreading temperature, the maximum temperature of the strain-induced martensite transformation is higher than the 3D printing powder spreading temperature, and the stacking fault energy is greater than or equal to 18mJ / m 2 , the nickel equivalent and chromium equivalent are in the austenite phase region on the Schaeffler organization diagram.
3. A method for preparing metal powder for magnetically coupled 3D printing, characterized in that: The following steps are involved: S1. Design the composition of metal materials so that their martensitic transformation temperature is lower than the 3D printing powder laying temperature, their strain-induced martensitic transformation maximum temperature is higher than the 3D printing powder laying temperature, and their stacking fault energy is greater than or equal to 18mJ / m 2 , the nickel equivalent and the chromium equivalent are in the austenite phase region on the Schaeffler organization diagram; S2. Melting: melting metal materials according to the designed composition; S3, powder processing, converting the smelted metal into metal powder; S4, subjecting the metal powder to a solution treatment and a water quenching treatment to obtain a substantially non-magnetic metal powder; S5. Make the basically non-magnetic metal powder generate magnetism after being subjected to force.
4. The method for preparing metal powder for magnetically coupled 3D printing according to claim 3, characterized in that: The step S1 of designing the metal material composition comprises the following steps: S11. Component range of preliminary design materials; S12, calculating the martensitic transformation temperature of the material, and selecting a composition range whose martensitic transformation temperature is lower than the 3D printing powder laying temperature; S13, within the composition range selected in step S12, calculating the maximum temperature of the strain-induced martensitic transformation of the material, and selecting a composition range in which the maximum temperature of the strain-induced martensitic transformation is higher than the 3D printing powder laying temperature; S14: Calculate the stacking fault energy of the material within the range of components selected in step S13, and select a stacking fault energy greater than or equal to 18 mJ / m 2 The range of ingredients; S15, within the component range selected in step S14, calculating the nickel equivalent and the chromium equivalent of the material, and selecting a component range in which the nickel equivalent and the chromium equivalent are in the austenite phase region on the Schaeffler organization diagram; S16. Calculate the chromium-nickel ratio of the material within the range of components screened in step S15, sort the components screened in step S15 according to the chromium-nickel ratio, and select the components with the highest chromium-nickel ratio.
5. The method for preparing metal powder for magnetically coupled 3D printing according to claim 4, characterized in that: The maximum temperature of the strain-induced martensitic transformation of the material in step S1 is denoted by M d30 Representative, M. d30 That is, the temperature at which austenite transforms to 50% martensite when the true strain is 30%; the stacking fault energy of the material in step S1 is represent, is the stacking fault energy at room temperature 300K.
6. The method for preparing metal powder for magnetically coupled 3D printing according to claim 5, characterized in that: The martensitic transformation start temperature of the material is calculated as follows: M s =1350-1655(w C +w N )-33w Mn -28w Si -42w Cr -61w Ni The maximum temperature of the strain-induced martensitic transformation of the material is calculated as follows: <h2 style=";text-align:left;direction:ltr">M<h2 style=";text-align:left;direction:ltr"> d30 <h2 style=";text-align:left;direction:ltr"> =413-462(w<h2 style=";text-align:left;direction:ltr"> C <h2 style=";text-align:left;direction:ltr"> +w<h2 style=";text-align:left;direction:ltr"> N <h2 style=";text-align:left;direction:ltr"> )-8.1w<h2 style=";text-align:left;direction:ltr"> Mn <h2 style=";text-align:left;direction:ltr"> -9.2w<h2 style=";text-align:left;direction:ltr"> Si <h2 style=";text-align:left;direction:ltr"> -13.7w<h2 style=";text-align:left;direction:ltr"> Cr <h2 style=";text-align:left;direction:ltr"> -9.5w<h2 style=";text-align:left;direction:ltr"> Ni <h2 style=";text-align:left;direction:ltr"> -18.5w<h2 style=";text-align:left;direction:ltr"> Mo The stacking fault energy of the material is calculated as follows: The nickel equivalent of the materials is calculated as follows: No eq =in Ni +30(in C +in N )+0.5(in Mn +in Cu +in Co ) The chromium equivalent of the materials is calculated as follows: Cr eq =w Cr +1.5w Si +w Mo Among them, w C 、w N 、w Mn 、w Si 、w Cr 、w Ni 、w Mo 、w Cu 、w Co Respectively represent the weight percentage of C, N, Mn, Si, Cr, Ni, Mo, Cu, and Co elements in the metal alloy; is the stacking fault energy at room temperature 300K, is the stacking fault energy of pure γ-Fe at room temperature.
7. The method for preparing metal powder for magnetically coupled 3D printing according to claim 3, characterized in that: The melting in step S2 is vacuum induction melting.
8. The method for preparing metal powder for magnetically coupled 3D printing according to claim 3, characterized in that: The powder processing in step S3 is inert gas atomization.
9. The method for preparing metal powder for magnetically coupled 3D printing according to claim 3, characterized in that: The method of making the substantially non-magnetic metal powder magnetic after being subjected to force in step S5 is shot blasting / shot peening.
10. The method for preparing metal powder for magnetically coupled 3D printing according to claim 9, characterized in that: The spraying speed of the metal powder material for shot blasting / shot peening is 10-160 m / s.
Citation Information
Patent Citations
Magnetic force combined 3D printing method
CN116099983A
Selective magnetization 3D printing method
CN116237537A
Magnetic composite body with ferromagnetic section and weak or non-magnetic section e.g. for car fuel or oil control device
DE19650710A1
Strain induced transformation method for austenitic stainless steel, and production of magnetic member
JP1998102140A
Martensitic nanocrystal alloy steel powder, bulk material thereof, and method for producing them
JP2008208401A
